PENGARUH HARGA DAN KUALITAS PELAYANAN TERHADAP KEPUASAN PELANGGAN PADA USAHA CATERING BLASTA FOOD AND LOUNGE BEKASI JAWA BARAT - Bunga Ayu Nirwana; Ardianto (JURNAL RUMPUN MANAJEMEN DAN EKONOMI, 2026)
The purpose of this study is to determine the effect of price and service quality on customer satisfaction at the catering business Blasta Food and Lounge. This research employed a quantitative descriptive method, with data collected through questionnaires. The population in this study consisted of all customers of Blasta Food and Lounge Bekasi, West Java, totaling 130,854 customers based on the latest data from the 2023–2025 period, as seen from the realization data of the number of orders during that year. Using the Slovin formula with a 10% margin of error, the sample size obtained was 99 respondents.The data analysis techniques used in this study included validity testing, reliability testing, classical assumption testing, multiple regression analysis, multiple correlation coefficient analysis, coefficient of determination analysis, and hypothesis testing. The results showed that Price (X1) had an effect on Customer Satisfaction (Y) of 60.0%, with the hypothesis test result showing that the calculated t-value was greater than the t-table value (13.022 > 1.660). Therefore, H0₁ was rejected and Ha₁ was accepted.The results of the partial correlation coefficient test between Service Quality (X2) and Customer Satisfaction (Y) obtained a value of 0.798, indicating that both variables had a strong relationship. The coefficient of determination value was 0.636 or 63.6%, while the remaining 36.4% was influenced by other factors. The results of the partial hypothesis test (t-test) for the Service Quality variable (X2) on Customer Satisfaction (Y) showed that the calculated t-value was greater than the t-table value (13.022 > 1.660), with a significance value of less than 0.001 (0.000 < 0.05).Furthermore, the results of the simultaneous hypothesis test (F-test) for the variables Price (X1) and Service Quality (X2) on Customer Satisfaction (Y) showed that the calculated F-value was greater than the F-table value (103.763 > 3.939), with a significance value of less than 0.001 (0.000 < 0.05). Therefore, H0₃ was rejected and Ha₃ was accepted, meaning that there was a significant positive effect of price and service quality on customer satisfaction.